Thromboembolism Triggered by a Combination of Electronic Cigarettes and Oral Contraceptives: A Case Report and Review of Literature - Olaniyi Fadeyi MD; Anantbir Randhawa MD; Abhirami Shankar MD; Christine Garabetian MD; Harpreet Singh MD; Antonio Topacio MD (SAGE Publishing, 2023)
Genetic predisposition, oral contraceptive (OCP) use, tobacco smoking, cancers, and trauma are well-known triggers for hypercoagulability and thromboembolism. Multiple reports have been published on the health risk of combining OCP and traditional cigarettes smoking in the context of thromboembolism. However, limited information is available on the health consequences of combining OCP use with electronic cigarettes. Here, we report a case of a young female patient with a past medical history of ovarian cysts and electronic cigarettes use who came into the hospital with a complaint of "recurrent seizures" and tachycardia. This patient was subsequently diagnosed with bilateral pulmonary emboli, subacute cerebrovascular accident (CVA), and possible patent foramen ovale. Therapeutic Lovenox was initiated. Reasons to educate young females on the risks of combining OCP and electronic cigarettes use were explained.